Radical right populism and the sociology of punishment: Towards a research agenda - Hamilton, Claire (Punishment & society, 2023)
The recent populist ‘explosion’ in the US, UK and Europe has pushed radical right populist movements to the centre of western politics. Given criminology's long experience of penal populism in the 1980s and subsequent decades, these developments raise important questions as to the role of sociology of punishment, and the wider discipline of criminology, in responding to far-right populism. This article aims to takes stock of the existing literature on this phenomenon with a view to proposing a tentative criminological research agenda that may contribute to our understanding of the recent rise of authoritarian politics in Europe, the UK and US. While highlighting the continued salience of the emotions in contemporary ‘security populism’, the article cautions against what has been described as a ‘pathologising’ approach to research in this area. Building on this, the paper advances an argument for a criminological research agenda based on a post-dualistic understanding of political affects that seeks to move the analytic focus beyond negativity.